2021
DOI: 10.3390/nu13103584
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Malnutrition and Oral Health in Older People: A Systematic Review

Abstract: The aim of this systematic review was to examine the association between malnutrition and oral health in older people (≥ 60 years of age). A comprehensive systematic literature search was performed in four databases (PubMed, CINAHL, Dentistry and Oral Sciences Source, and Embase) for literature from January 2000 to May 2020. Both observational and intervention studies were screened for eligibility. Two reviewers independently screened the search results to identify potential eligible studies, and assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…In this study, we found that diabetic patients from Oaxaca presented the highest prevalence of edentulism. Although, from a traditional perspective, the importance of keeping teeth in good functional condition lies in its positive impact on a better quality of life [24] and the fact that association of edentulism with chronic diseases, in addition, other studies have documented the negative impact of edentulism on people's nutritional status [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that diabetic patients from Oaxaca presented the highest prevalence of edentulism. Although, from a traditional perspective, the importance of keeping teeth in good functional condition lies in its positive impact on a better quality of life [24] and the fact that association of edentulism with chronic diseases, in addition, other studies have documented the negative impact of edentulism on people's nutritional status [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that diabetic patients from Oaxaca presented the highest prevalence of edentulism. Although, from a traditional perspective, the importance of keeping teeth in good functional condition lies in its positive impact on a better quality of life [24] and the fact of the association of edentulism with chronic diseases, in addition, other studies have documented the negative impact of edentulism on people's nutritional status [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that poor oral health affects the general health in terms of higher prevalence of pneumonia, and increased severeness of already existing diabetes mellitus [9,10]. Connections between poor oral health and cardiovascular diseases [11], involuntary weight loss [12], and malnutrition [13] have also been of interest in recent research. However, the ability to perform daily oral self-care often decreases with age [14].…”
Section: Introductionmentioning
confidence: 99%